Pertanggungjawaban Pidana Pelaku Tindak Pidana Pemalsuan Uang Dihubungkan dengan Undang-undang Nomor 7 Tahun 2011 tentang Mata Uang - Nisa Zahra Alifah; Chepi Ali Firman Z (UNISBA Press, 2022)
Abstract. Money basically has a function as a medium of exchange, a store of value, a unit of account, and a measure of delayed payments, which in essence determines how the economy of a country can help support its people. One of the crimes against currency is the crime of counterfeiting money. Where the crime of counterfeiting money is not only detrimental to society but also has an impact on political, social and economic stability. Based on the above phenomenon, this research focuses on the problem of criminal liability for the perpetrators of the crime of counterfeiting money, especially in the decision Number 165/Pid.b/2020/Pn Cms and the problem of how the implications of Article 244 of the Criminal Code are. This study uses a normative juridical research method, this research was conducted on the application of Law No. 7 of 2011 concerning Currency and the Criminal Code Articles 244 and 245 in law enforcement of the crime of counterfeiting money. The result of this research is that the provision of criminal sanctions against the perpetrators of the crime of counterfeiting money in the decision No. 165/Pid.B/2020/Pn Cms is still far from the maximum penalty demanded in the indictment of the perpetrator. And the implications of implementing the Criminal Code in law enforcement for the crime of counterfeiting money do not have an effective impact, especially in the Criminal Code criminal sanctions against the crime of counterfeiting money are only punished with a single criminal sanction, namely only imprisonment so that the risk of recidivism by the perpetrator will be higher. In essence, the results of this study are that law enforcement of the crime of counterfeiting money in Indonesia is still relatively weak, and relatively light so that it does not provide a deterrent effect. Abstrak. Uang pada dasarnya memiliki fungsi sebagai alat tukar, alat penyimpan nilai, satuan hitung, dan ukuran pembayaran yang tertunda, yang pada intinya uang menjadi penentu bagaimana perekonomian sebuah negara yang dapat membantu menghidupi rakyat rakyatnya melihat dari fungsi uang yang sangat penting hal tersebut mengakibatkan terjadinya banyak tindak pidana terhadap mata uang salah satunya adalah tindak pidana pemalsuan uang. Dimana tindak pidana pemalsuan uang bukan hanya merugikan masyarakat tetapi juga berdampak kepada stabilitas politik, sosial, dan ekonomi. Berdasarkan fenomena diatas maka penelitian ini berfokus pada masalah pertanggungjawaban pidana pelaku tindak pidana pemalsuan uang khususnya dalam putusan Nomor 165/Pid.b/2020/Pn Cms serta masalah mengenai bagaimana implikasi Pasal 244 KUHP. Penelitian ini menggunakan metode penelitian yuridis normatif, penelitian ini dilakukan terhadap penerapan Undang-Undang No.7 Tahun 2011 Tentang Mata Uang dan KUHP Pasal 244 dan245 dalam penegakan hukum tindak pidana pemalsuan uang. Hasil dari penelitian ini adalah Pemberian sanksi pidana terhadap pelaku tindak pidana pemalsuan uang dalam putusan No.165/Pid.B/2020/Pn Cms masih jauh dari pidana maksimum yang dituntut dalam dakwaan pelaku. Dan implikasi dari diimplementasikan KUHP dalam penegakan hukum tindak pidana pemalsuan uang tidak berdampak secara efektif terlebih lagi di dalam KUHP sanksi pidana terhadap tindak pidana pemalsuan uang hanya dipidana dengan sanksi pidana tunggal yaitu hanya sanksi pidana penjara saja sehingga resiko terjadinya residivis oleh pelaku akan lebih tinggi. Pada intinya hasil dari penelitian ini adalah penegakan hukum tindak pidana pemalsuan uang di Indonesia masih terbilang lemah, dan tidak memberikan efek jera.